Reconciling Tradition and Modernity: A Critical Review of Sexuality Education in the Indonesian Pesantren Context - Muhammad Erix; Kasful Anwar (Lembaga Bale Literasi, 2025)
This study aims to analyze teachers’ and parents’ perceptions regarding the causal factors of students’ deviant behavior at SMK Negeri 5 Sarolangun. The research employed a qualitative descriptive approach to obtain an in-depth understanding of the phenomenon based on the experiences and perspectives of the informants. Data were collected through semi-structured interviews, participatory observation, and documentation. The informants consisted of guidance and counseling teachers, homeroom teachers, and parents of students who had committed disciplinary violations. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The findings revealed that students’ deviant behavior manifested in various forms, including tardiness, uniform violations, academic disengagement, smoking on school premises, verbal misconduct, bullying, and cheating. Teachers perceived family disharmony, lack of parental supervision, and negative peer influence as the primary causal factors. In contrast, parents emphasized insufficient school supervision, inconsistent disciplinary enforcement, and weak character education as contributing factors. Nevertheless, both teachers and parents agreed that peer influence, social media exposure, and adolescents’ emotional instability significantly affected students’ behavior. The study concludes that strengthening collaboration and communication between schools and families is essential in addressing deviant behavior and fostering students’ moral development.